Fractal Yagi-Uda antenna for WLAN applications - Amerrul Zabri; M. K. A. Rahim; F. Zubir; N. M. Nadzir; H. A. Majid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper describes the development of a Fractal printed Yagi-Uda antenna for Wireless Local Area Network (WLAN) applications operating at 2.4 GHz frequency. In miniaturizing the dimensions of an antenna, fractal method is applied where the 1st iteration and 2nd iteration is implemented. The Computer Simulation Technology (CST) software is used as the platform to design and simulate the antenna. The substrate material used is the FR-4 board which has a dielectric constant of 5.4, the thickness of 1.6mm and tangent loss of 0.019. The antenna performance interm of the reflection coefficient, radiation pattern and gain are compared and analyzed. For the 1st iteration, 22.81% of reduction size has been achieved and 30.81% reduction of the antenna size for 2nd iteration has been achieved.